VENDOR-CAPACITY, PERCEIVED-FAMILIARITY, PERCEIVED-REPUTATION, DAN PERSONAL-VALUES SEBAGAI FAKTOR PEMBEDA PADA KELOMPOK KONSUMEN BAGI TERCAPAINYA ONLINE CUSTOMERS’ TRUST (STUDI PADA PENGGUNA LAZADA DI INDONESIA) - Yosi Afandi; Musthofa Hadi; Rizky Kurniawan Murtiyanto (Politeknik Negeri Malang, 2017)
The objectives are (1). Find the determinant variables that discriminate the consumers’ group on trusting or not to the online-transactions, among the dependent variables which consist of vendor-capacity, perceived-familiarity, perceived-reputation, and personal values. (2). Find the most differing variable from those determinant variables found, and (3). Find the effective strategy to overcoming the e-trust barriers in Indonesian Lazada user. The data collected from 85 samples of Indonesians that experiencing the e-commerce transactions. Many questioners were spread by mailed and also direct spreading to meet the data quota. The data analysis that used were Discriminant Analysis and Crosstab Analisis. Result of this study show that from four predicting variables, there are only two variables that determinant the consumers’ choise to trust or not to the online-transactions; vendor-capacity and perceived-familiarity,- which has significant influence for this case. The consumers’ perceived-familiarity was found as the most influencing variables that could discriminate the trust of the customers to online-transactions. So, the vendors’ strategy should be held to educate the customer and maximizing the customers’ relationship programs, beside continous improvement of the vendors’ capacities as well.